Hart sobre o princípio de Mill - Ferrari, Patricia Medianeira Mino (2011)
This work aims to investigate the relationship between legality and morality in the view of the Law theorist Herbert L.A Hart. We analyze the claims which arouse as a reaction against the polemical Report of the Wolfenden Committee on Homosexual Offences and Prostitution from 1957. This report addresses the decriminalization of male homosexual conduct and prostitution based on the argument that there should be a field of private morality and immorality which did not belong to the legal scope. First, we analyze the works by Hart which deal with the relationship between law and morals. Then, we investigate the Harm Principle or Principle of Civil Liberties, supported by John Stuart Mill in his work On Liberty , and which served as a support for the conclusions of the Report. Finally, we analyze the claims made by Hart on behalf of a mitigated form of Mill‟s Principle, as well as the impact of these claims among theorists such as Patrick Devlin, Peter Cane and Neil Mac Cormick.